2020
DOI: 10.1093/jhered/esaa031
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Features of Parthenogenetic Animals

Abstract: Evolution without sex is predicted to impact genomes in numerous ways. Case studies of individual parthenogenetic animals have reported peculiar genomic features that were suggested to be caused by their mode of reproduction, including high heterozygosity, a high abundance of horizontally acquired genes, a low transposable element load, or the presence of palindromes. We systematically characterized these genomic features in published genomes of 26 parthenogenetic animals representing at least 18 independent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(116 citation statements)
references
References 118 publications
15
101
0
Order By: Relevance
“…We tested these predictions by comparing the genomes of five independently derived parthenogenetic stick insect species in the genus Timema with their close sexual relatives ( Figure 1). These replicate comparisons allowed us to solve the key problem in understanding the consequences of parthenogenesis for genome evolution: separating the consequences of parthenogenesis from lineage specific effects ( 17 ) . Timema are wingless, plant-feeding insects endemic to western North America.…”
mentioning
confidence: 99%
“…We tested these predictions by comparing the genomes of five independently derived parthenogenetic stick insect species in the genus Timema with their close sexual relatives ( Figure 1). These replicate comparisons allowed us to solve the key problem in understanding the consequences of parthenogenesis for genome evolution: separating the consequences of parthenogenesis from lineage specific effects ( 17 ) . Timema are wingless, plant-feeding insects endemic to western North America.…”
mentioning
confidence: 99%
“…The genome-wide heterozygosity of D. stevensoni matches to some extent an earlier study on intra-individual divergence in three nuclear genes of D. stevensoni . The finding of almost 1% heterozygosity in D. stevensoni is remarkable, given that all previous genome-wide estimates for asexual arthropods that did not evolve via hybridization revealed extremely low levels of heterozygosity (Jaron et al 2020). Yet heterozygosity is clearly less than the estimates for parthenogenetic species with known hybrid origin (1.73-8.5%) or polyploidy (1.84%-33.21%) (Jaron et al (2020), supporting the view that D. stevensoni is neither a hybrid nor a polyploid.…”
Section: Results and Discussion First Ostracod Reference Genomes Andmentioning
confidence: 76%
“…The finding of almost 1% heterozygosity in D. stevensoni is remarkable, given that all previous genome-wide estimates for asexual arthropods that did not evolve via hybridization revealed extremely low levels of heterozygosity (Jaron et al 2020). Yet heterozygosity is clearly less than the estimates for parthenogenetic species with known hybrid origin (1.73-8.5%) or polyploidy (1.84%-33.21%) (Jaron et al (2020), supporting the view that D. stevensoni is neither a hybrid nor a polyploid. Asexual reproduction in ostracods is thought to be apomictic (Chaplin et al 1994), implying that observed heterozygosity levels are largely depend on the relative impact of heterozygosity losses from gene conversion and heterozygosity gains from new mutations.…”
Section: Results and Discussion First Ostracod Reference Genomes Andmentioning
confidence: 76%
See 2 more Smart Citations